Logos of South Asian Countries: A Visual Aesthetic and Symbolic Significance - Hamal, Koshal (Journal of Fine Arts Campus, 2023)
A national logo is a visual representation of a country, and it signifies the most powerful visual language of any country in the world. All the countries have their own logo to represent their country in visual form. In the context of each country in South Asia, a national logo is categorized as a national emblem. The national emblems of South Asian countries have different and unique meanings and are made with different cultural, religious, natural, and historical motifs and shapes. The main objective of this paper is to identify the visual aesthetic and symbolic significance of the national emblems of each South Asian country. The visual aesthetic contains elements of composition, color, shapes, and the essential rules of a logo, while the symbolic significance contains the symbolic meaning of each motif used for the entire logo of a South Asian country. This study finds that a country's culture, religion, and history should not be disconnected from the national emblem because the national emblem creates unique values for a country. A national emblem is like a mirror of a country, which represents the appropriate visual symbol of a country. This study is an analytical study based on qualitative method.